DESCRIPTION OF CHARACTERISTICS FACTORS AFFECTING THE COMPLICATION OF DIABETES MELLITUS PATIENTS IN ABDUL WAHAB HOSPITAL SJAHRANIE SAMARINDA PERIOD MEI - JUNI 2019 - zakaria sodiq; Danial Danial; Yuliana Rahmah Retraningrum (Jurnal Ilmu Kesehatan, 2020)
ABSTRACTDiabetes Mellitus is a chronic disease that most often causes death. Patients with diabetes mellitus who are referred to hospitals have already experienced both macrovascular and microvascular complications. This study aims to determine the risk factors and types of complications that occur in patients with Diabetes Mellitus. This research uses descriptive observational design, with purposive sampling technique. The sample of this study was Diabetes Mellitus patients with complications in Abdul Wahab Sjahranie Hospital Samarinda. There are 52 respondent who met the inclusion and exclusion criteria. Overall data on the characteristics of patients based on age with the most complications are patients aged <60 years. As many as 37 people (71.2%) and the characteristics of patients based on sex most experienced complications were female sex patients, as many as 36 people (69.2%). There is a relationship between student perceptions of the learning environment on campus with an achievement index.